2009
DOI: 10.1037/a0015823
|View full text |Cite
|
Sign up to set email alerts
|

The relations between parents’ Big Five personality factors and parenting: A meta-analytic review.

Abstract: To investigate the association between Big Five personality factors and three dimensions of parenting-warmth, behavioral control, and autonomy support-the authors conducted meta-analyses using 5,853 parent-child dyads that were included in 30 studies. Effect sizes were significant and robust across mother and father reports and across assessment methods of parenting (self-report versus observations) but were generally small in magnitude. Higher levels of Extraversion, Agreeableness, Conscientiousness, and Open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
418
5
29

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 422 publications
(527 citation statements)
references
References 93 publications
39
418
5
29
Order By: Relevance
“…A meta‐analysis has shown that homozygotes for the BDNF Val allele are characterized by higher levels of neuroticism (Frustaci, Pozzi, Gianfagna, Manzoli, & Boccia, 2008), and higher levels of neuroticism have been linked to lower levels of warmth (Prinzie et al., 2009). Additionally, it has been found that less neurotic fathers change their use of positive control according to their child's level of effortful control, while fathers with relatively high levels of neuroticism do not (Karreman et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis has shown that homozygotes for the BDNF Val allele are characterized by higher levels of neuroticism (Frustaci, Pozzi, Gianfagna, Manzoli, & Boccia, 2008), and higher levels of neuroticism have been linked to lower levels of warmth (Prinzie et al., 2009). Additionally, it has been found that less neurotic fathers change their use of positive control according to their child's level of effortful control, while fathers with relatively high levels of neuroticism do not (Karreman et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Various factors have been shown to affect parental warmth, such as heritability (Klahr & Burt, 2014); the parent's personality (Prinzie, Stams, Deković, Reijntjes, & Belsky, 2009); the child's behavior (Barnett, Gustafsson, Deng, Mills‐Koonce, & Cox, 2012); and socioeconomic status (SES), race, and a dangerous neighborhood (Pinderhughes, Nix, Foster, & Jones, 2001). However, there is limited knowledge about which specific genes the heritability estimate represents, how the factors that affect warmth interact, how they affect differential parenting, and how they affect fathers, as most of the research to date has been done on mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Effective limit-setting, as opposed to either too lax or too rigid parental control and psychological manipulation, reflects the type of developmentally appropriate behavioral control and regulation of one's child that is typically associated with authoritative parenting and that avoids the negative control cycles associated with deteriorating parentchild relationships. Although a connection between parental C and limit-setting is intuitively appealing, it may be that child C is correlated with authoritative parenting, because the child models the parental personality and/or because of an evocative correlation (i.e., the child's C elicits or facilitates authoritative parenting; Prinzie et al, 2009). Thus, the avoidance of adolescent snares, such as those identified by Moffit and her colleagues, may involve a "web" of parental and child C, which in turn jointly facilitates authoritative parenting and more effective monitoring and limitsetting.…”
Section: Processes In Adolescencementioning
confidence: 99%
“…(a) Parental C. Adult C may be related to central indicators of parenting-including warmth, more effective behavioral control, and autonomy support, as well as family management-all of which might decrease children's exposure to stressors and increase their ability to cope with stress (Prinzie et al, 2009). In turn, the specific behaviors in which C parents engage may lead to healthpromoting family contexts (Huver, Otten, de Vries, & Engels, 2010), and some evidence suggests that the caregiver's C is especially salient in the management of risk.…”
Section: Processes In Childhoodmentioning
confidence: 99%
See 1 more Smart Citation